Multilayered Defense in HLA-B51-Associated HIV Viral Control - Zhang, Y; Peng, Y; Yan, H; Xu, K; Saito, M; Wu, H; Chen, X; Ranasinghe, S; Kuse, N; Powell, T; Zhao, Y; Li, W; et al. (2011)
Polymorphism in the HLA region of a chromosome is the major source of host genetic variability in HIV-1 outcome, but there is limited understanding of the mechanisms underlying the beneficial effect of protective class I alleles such as HLA-B57, -B27, and -B51. Taking advantage of a unique cohort infected with clade B' HIV-1 through contaminated blood, in which many variables such as the length of infection, the infecting viral strain, and host genetic background are controlled, we performed a comprehensive study to understand HLA-B51-associated HIV-1 control.We focused on the T cell responses against three dominant HLA-B51-restricted epitopes: Gag327-345(NI9) NANPDCKTI, Pol743-751(LI9) LPPVVAKEI, and Pol283-289(TI8) TAFTIPSI. Mutations in all three dominant epitopes were significantly associated with HLA-B51 in the cohort. A clear hierarchy in selection of epitope mutations was observed through epitope sequencing. L743I in position 1 of epitope LI9 was seen in most B51+ individuals, followed by V289X in position 8 of the TI8, and then, A328S, in position 2 of the NI9 epitope, was also seen in some B51+ individuals. Good control of viral load and higher CD4+ counts were significantly associated with at least one detectable T cell response to unmutated epitopes, whereas lower CD4+ counts and higher viral loads were observed in patients who had developed escape mutations in all three epitopes or who lacked T cell responses specific to these epitope(s). We propose that patients with HLA-B51 benefit from having multiple layers of effective defense against the development of immune escape mutations. Copyright © 2011 by The American Association of Immunologists, Inc.